An in vitro study of coagulation evaluation in obstetric hemorrhage for pregnancy-induced hypertension with coagulation and platelet function analyzer - Caihong Cao; Maimaitijiang Yusupu; Yaoqi Wang; Yonghao Yu (Taylor & Francis Group, 2024)
This study aimed to establish in vitro hemodilution and resupplementation assays for obstetric hemorrhage in pregnancy-induced hypertension (PIH) and to monitor the coagulation function dynamically using a coagulation and platelet function analyzer. Forty-seven singleton pregnant women were divided into normal (n = 24) and PIH (n = 23) groups. Peripheral blood samples were used to construct the assays, and the activated clotting time (ACT), clotting rate (CR), and platelet function index (PF) were measured. The results showed that the baseline ACT was higher in the PIH group (p < 0.01). Hemodilution assays showed decreased ACT and increased CR and PF, with ACT changes significantly lower in the PIH group (p < 0.05). CR changed most in both groups at lower dilution ratios (35% to 50%), while ACT changed most at a higher dilution ratio (75%). In the resupplementation assay, ACT exhibited the most significant response. The analyzer effectively detected differences between pregnant women with and without PIH. Thus, we need to pay more attention to the changes of ACT in the actual clinical application to assess the coagulation status of parturients.